UNVEILING THE POWER OF PRICE ELASTICITY: THE KEY TO SUCCESSFUL BUSINESS STRATEGIES AND PRICING DECISIONS - Rahmat, Hayatul Khairul (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
Price Elasticity of Demand (PED) is a fundamental concept in microeconomics that measures consumer responsiveness to price changes of a good or service. In a managerial context, a deep understanding of PED is essential for making decisions related to pricing, production planning, and revenue forecasting. This paper comprehensively discusses the determinants of price elasticity of demand, its applications across various sectors, and how managers can leverage elasticity information to develop optimal pricing strategies. Case studies, such as Apple and Indonesian food markets, provide practical insights into how demand elasticity influences everyday business decisions. In conclusion, price elasticity of demand is not just an abstract theory, but a crucial practical tool for managers aiming to enhance competitiveness and business sustainability in dynamic markets.